Ownership Structure and Earning Management – A Literature Review - Andriani, Wery; Amelia, Novi; Primadyan, Maretha (Universitas Batanghari Jambi, 2025)
This study aims to provide insight into earnings management in companies with various ownership types. This empirical research focuses on a literature review of the relationship between earnings management and corporate ownership. The results of this study found that differences in corporate ownership can influence decisions related to earnings management.